Nonparticipation as a Social-Cultural Lifestyle - Babajanyan, Levon (Bulletin of Yerevan University E: Philosophy, Psychology, 2014)
In current postindustrial societies after some civilizational, political and anthropological transformations specific social-cultural space is formed, where conducive conditions for distribution of the lifestyle of nonparticipation occurred. In the article the social-cultural lifestyle of nonparticipation is viewed as a special form of sociality, which dictates such standards of the life, which are in contradiction to the vital activity of the citizen. But the social-cultural lifestyle of nonparticipation is peculiar for the transformational societies, where specific conditions for the distribution of the lifestyle of nonparticipation exist. But if the social-cultural lifestyle of nonparticipation in the postindustrial societies shows the stability and the solidity of social system, the social-cultural lifestyle of nonparticipation in the transformational societies may lead to the unpredictable and uncertain results.
Keywords: lifestyle of nonparticipation, social-cultural environment, postindustrial civilization, consumer society, transformational society, citizen, political speechlessness, silent majority